Comment on: “Chemostratigraphic constraints on early Ediacaran carbonate ramp dynamics, Río de la Plata craton, Uruguay” by Aubet et al. Gondwana Research, Volume 22, Issues 3-4, November 2012, Pages 1073-1090 - Gaucher, Claudio (2013)
The Arroyo del Soldado Group of Uruguay is a key unit for unraveling several, still unsolved cardinal problems in Neoproterozoic research. Thus, we welcome in principle publications contributing to our knowledge of this and other units. Regarding Aubet et al.'s (2012) paper, we contest their age assumptions and chemostratigraphic inferences and thereby call into question the core message of the paper. Moreover, we also show below that it does not make proper acknowledgement of sources.